A redesign of hospice social care services. Issue 2 (1st September 2011) - Thomas, Martin; Widlake, Jutta
Abstract : Introduction: The social care resource of the typical hospice has developed in steps over a period of time, as and when funding becomes available. As a consequence of this the structures of different teams and departments are varied and often follow no clear model. This was the situation faced at the hospice of this study team, who identified that this carried with it certain risks, both to service users and to the organisation. In order to address those risks, changes were needed, and a stronger structure developed for the social care provision of the hospice. Aims: To carry out a systematic review and design of a hospice social care service. Methods: A focus group carried out a literature search and multidisciplinary planning sessions. A business plan was developed and put into place. Results: Social care was restructured around a 4 level model. The qualified social worker to social care assistant ratio was altered to reflect the need for clear assessment and delegation, in order thet the risks were addressed. Discussion: Hospice social care brings with it a high level of risk. This risk can be lessened if the appropriate structure is in place ensuring that patient's needs are at the focus of care. The 4 level model provides a structure to rebuild the service, and a clarity to ensure that the appropriate competencies, knowledge and skills are in place to deliver care safely. Conclusion: The use of the 4 level model to restructure and redesign the hospice's social care service ensured a patient needs focus. The structure also allowed clear identification of the knowledge and skills needed across the health and social care workforce for safe patient assessment and care.